Rancang Bangun Robot Omni Wheel Penyedot Debu Menggunakan Sensor Accelerometer Berbasis Mikrokontroler ATMega16 - Ivan Suwanda . (Faculty of Engineering, Universitas Tanjungpura, 2014)
In the current technological developments , especially in the field of robotics and communications technology develops very rapidly , a lot of robots and communication tools that are created with advanced technology . At the present time communication tools has created a lot of communication tools such as a smartphone that has advanced features and supported with a variety of sensors that are already embedded inside as well as the advancement of robotic technology that is able to help people ease the burden of human work . implementation of these two elements is to make a robot vacuum cleaner uses omni wheel which can move in any direction without performing complex movements and controlled using the accelerometer sensor android smartphone via Bluetooth RC controller application contained in Playstore so that the robot moves following the movement of the next smartphone Media Conductor between a smartphone and a robot using bluetooth HC - 05 . From the data obtained after performing several experiments bluetooth can capture signals up to a maximum distance of 25 meters , then the success of the movement of the robot at 82.31 % . With the tilt sensitivity of the accelerometer at 5 ° robot is quite reliable maneuver to remove dust or dirt with a small back and forth movement methodKeywords– omniwheel, accelerometer, bluetooth controller